Síntese e avaliação de arranjos supramoleculares de triazenos monocatenados e complexos com os cátions Co3+, Cu2+, Ag+ e Au+ - Behm, Mariana Boneberger (2010)
Triazenes ligands substituted by terminal aryl groups in the diazoamine chain [ N=N N(H) ] containing NO2 group substituted in different position and ortho C(O)NH2 on aryl ring was evaluated on the occurrence of intermolecular interactions through hydrogen links. The research was based primarily on X-ray diffraction in single crystal to analyze structurally the occurrence of self-assembles supramolecular architectures on solid state. This work presents the synthesis and investigation of molecular and crystal structure of eleven new compounds. The pre-ligands 1-(2-amidofenil)-3-(2-nitrofenil)triazeno (I), 1-(2-amidofenil)-3-(4-nitrofenil)triazeno (II) e 1-(2-amidofenil)-3-(3-nitrofenil)triazeno (III), the cobalt(III) complexes: {Co[C(O)NHC6H4NNNC6H4NO2](C2H8N2)2}{Cl}.CH3OH (1), {Co[C(O)NHC6H4NNNC6H4NO2](C2H8N2)2}{Cl}.H2O (2) and {Co[C(O)NHC6H4NNNC6H4NO2](NH3)4}{NO3}.H2O (3), and silver(I) complexes: {Ag[C(O)NH2C6H4NNNC6H4NO2](C2H8N2)}{[C(O)NH2C6H4NNN(H)C6H4NO2]} (4) and {Ag[C(O)NH2C6H4NNNC6H4NO2](C2H8N2)]} (5), and cupper(II) complexes: {Cu4[C(O)NHC6H4NNNC6H4NO2]2[(OCH3)4]} (6) and gold(I) complexes: {Au[C(O)NH2C6H4NNNC6H4NO2](PC18H15)}{C5H5N} (7) e Au[C(O)NH2C6H4NNNC6H4NO2](PC18H15)] (8). Other complementary techniques were used to characterize the compounds, such as: infrared spectroscopy, 1H nuclear magnetic resonance spectroscopy, ultraviolet-visible spectroscopy, mass spectrometry, Raman spectroscopy and thermogravimetric analysis.